Impact of COVID-19 on the occurrence and exacerbation of cutaneous forms of lupus erythematosus: A review - Eleonora S. Mikheeva; Iuliia M. Golubeva; Ekaterina E. Radionova; Olga V. Zhukova; Irina M. Korsunskaya (ZAO "Consilium Medicum", 2023)
The article addresses the impact of the new coronavirus infection on the occurrence of cutaneous forms of lupus erythematosus (LE). Since the beginning of the COVID-19 pandemic, there has been an increase in the incidence of cutaneous LE worldwide, the emergence of new cases, and exacerbation and aggravation of the severity of existing ones. The pathogenesis of cutaneous LE, and the role of viral infections in its occurrence, mainly COVID-19, is reviewed. The need for the SARS-CoV-2 vaccination and its potential as a possible trigger is described. It is necessary to note the importance of clinicians in diagnosing LE since it is essential for the dermatologist to know the features of its course and be able to suspect and diagnose even the rarest forms of this disease. Proper awareness and correct diagnosis determine the optimal drug therapy and patient health in the future.